A Powerful Antidote, a Strange Camel and Turkish Pepper: Iberian Science, the Discovery of the New World and the Early Modem Czech Lands - Cerna, Jana (Early science and medicine, 2016)
This article analyses the reception of knowledge about new world nature, and, more specifically, the reception of Iberian scientific knowledge of nature in the Americas, in the early modem Czech lands. It shows how the process of the reception of information about nature in the new world differed among the urban classes, intellectuals and the nobility; particular attention is paid to herbals, cosmographical works and travel reports. On the one hand, the study reveals that the efforts of Central European intellectuals to interpret new world nature were limited by the lack of necessary data and experience, which led to some misinterpretations and simplifications. On the other hand, it shows these Central European scholars to be fully-fledged members of an information network, whose works share many of the same characteristics as Iberian and, in general, early modem European science.
Keywords: věda; Česká republika; History, 17th Century; Spain; Španělsko; zvířata; herbální medicína; Animals; Czech Republic; Portugalsko; lamy; Camelids, New World; znalosti; Capsicum; Austria-Hungary; Natural History; Amerika; Herbal Medicine; Portugal; Rakousko-Uhersko; Science; dějiny 17. století; Knowledge; Americas; Turkey; Turecko; přírodopis; History, 16th Century; dějiny 16. století